Impairment of Water Quality of Phuleli Canal, Sindh Pakistan: A Review - Ijaz, Muhammad Wajid; Mahar, Rasool Bux; Solangi, Ghulam Shabir; Panhwar, Sallahuddin; Ansari, Abdul Khalique (Mehran University Research Journal of Engineering and Technology, 2017)
Supply of quality water has been recognized as one of the water management practices. Clean water is not only essential for drinking and irrigation but also affects eco-services, groundwater aquifer and soil conditions. Hyderabad, a highly populated city of Pakistan is consuming large quantities of water and also disposing its untreated sewage and comingled solid waste in Phuleli canal. Similarly, many encroachments along the banks of Phuleli canal are directly impairing the water quality due to disposal of wastewater and other rejected materials. This canal irrigates Tando Muhammad Khan as well as some areas of district Badin. A review of many studies revealed that maximum of physio-chemical and biological parameters especially fecal Coliform (between 100-1600 MPN/100ml) and metal ions (Fe 1.90, Cd 0.004, Cr 0.082, Pb 0.045 and As 0.50 mg/l against WHO (World Health Organization) standards) were exceeding the prescribed permissible limits.This contaminated water is deteriorating the water quality and threatening the public health. Due to inadequate measures and apathy from responsible departments, water quality is being compromised especially during winter season, when low flows are released from Kotri Barrage, Kotri, Sindh. Without positive interventions and adherence of integrated approach, it is hard to ensure public health and sustainability of the canal system and agriculture depending upon this.